The Relationship Of Anxiety Level And Sleep Quality In Elderly Age In Karya Culture West Sitiung 1 Puskesmas Working Area Dharmasraya District 2024 - Metha Fitriyani; Candra Syah Putra; Rida Suriani (Jurnal EduHealth, 2024)
According to World Health Organization (WHO) data, approximately 18% of the world's population has experienced difficulty sleeping, it is estimated that around 20-50% of the elderly experience sleep quality problems. In Indonesia, around 50% of elderly people experience sleep disorders or 9.3 million elderly people aged 65 years. Meanwhile, the prevalence of sleep disorders in the elderly is quite high, namely around 67%, without realizing that these sleep disorders affect the quality of sleep in the elderly. The aim of this research was to determine the relationship between anxiety levels and sleep quality.This research used a correlational type of research with a cross sectional approach, with a sample of 69 elderly people who met the inclusion and exclusion criteria using a purposive sampling technique. Based on univariate analysis, most of the 40 respondents (58%) experienced moderate levels of anxiety, and almost all of the 69 respondents, namely 56 respondents (81.2%) had poor sleep quality. Based on bivariate analysis using the Spearman Rank test with data management using SPSS. The research results were obtained with a p-value = 0.041 <0.05, meaning that there is a relationship between the level of anxiety and the quality of sleep in elderly people in the western culture work area of the Sitiung 1 Health Center, Dharmasraya Regency in 2024. It can be concluded that the level of anxiety is very closely related to the quality of sleep, It is hoped that older people should not think too much about problems in their lives so that they do not have a high level of anxiety so they can have good quality sleep.